conductive paste
Patent Information
- Application Number
- JP2025058337
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
- Estimated Expiration
- 2045-03-31
AI Technical Summary
【0006】 ここに開示される導電性ペーストは、少なくとも導電性粒子と誘電体粒子とバインダ樹脂と分散媒体と分散剤とを含むグラビア印刷用の導電性ペーストである。この導電性ペーストは、せん断速度10000s-1における粘度が0.3Pa·s以下であり、かつ、周波数0.1Hzで動的粘弾性測定を行った際の位相角δが45°以下である。かかる導電性ペーストによると、グラビア印刷における転写不良とサドル立ちを抑制することができる。
Smart Images

Figure 2026165769000002 
Figure 2026165769000001
Abstract
Description
[Technical Field]
[0001] The technology disclosed herein relates to a conductive paste for gravure printing. [Background technology]
[0002] Electronic components such as multilayer ceramic capacitors (MLCCs) are widely used in various fields. In the manufacturing of this type of electronic component, a conductive paste is first printed onto the substrate surface. Next, a dry film is formed on the substrate surface by drying the conductive paste. Finally, the dry film is fired together with the substrate. This process allows for the production of electronic components with an electrode layer formed on the substrate surface.
[0003] Recently, gravure printing has been considered as a printing method for conductive paste. Gravure printing is said to be able to print conductive paste at about 10 times the speed of screen printing. In this gravure printing, a cylindrical plate cylinder with recesses (cells) on its outer surface is used. When this cylinder is immersed in conductive paste, the paste fills the cells. Then, the cylinder is rotated with a doctor blade in contact with its outer surface. This scrapes off any paste that has spilled out of the cells. Next, the outer surface of the cylinder is pressed against the substrate. This transfers the paste in the cells to the surface of the substrate. As a result, the conductive paste is printed on the surface of the substrate. An example of a conductive paste used in this gravure printing is disclosed in Patent Document 1. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2021-051916 [Overview of the project] [Problems that the invention aims to solve]
[0005] However, in gravure printing, there is a risk of defects occurring where a sufficient amount of paste is not transferred to the substrate (hereinafter referred to as "transfer defects"). In addition, in gravure printing, defects may occur where the central part of the conductive paste in the width direction becomes thin and the ends become thick (hereinafter referred to as "saddle buildup"). The technology disclosed herein was developed to solve the above-mentioned problems and aims to provide a technology for suppressing transfer defects and saddle buildup in gravure printing. [Means for solving the problem]
[0006] The conductive paste disclosed herein is a conductive paste for gravure printing comprising at least conductive particles, dielectric particles, a binder resin, a dispersion medium, and a dispersant. This conductive paste is subjected to a shear rate of 10,000 s. -1 The viscosity is 0.3 Pa·s or less, and the phase angle δ when dynamic viscoelasticity measurement is performed at a frequency of 0.1 Hz is 45° or less. Such a conductive paste can suppress transfer defects and saddle formation in gravure printing. [Brief explanation of the drawing]
[0007] [Figure 1] Figure 1 is a schematic diagram showing an example of a gravure printing apparatus. [Modes for carrying out the invention]
[0008] Preferred embodiments of the conductive paste disclosed herein will be described below. Matters other than those specifically mentioned herein that are necessary for carrying out the disclosed technology (e.g., methods for preparing the conductive paste, configuration of electronic components, etc.) can be carried out based on the general technical common sense of those skilled in the art.
[0009] [Conductive paste] 1. Overview The conductive paste disclosed herein is a conductive paste for gravure printing. This conductive paste contains at least conductive particles, dielectric particles, a binder resin, and a dispersion medium. Details of these components will be described later.
[0010] Next, the conductive paste disclosed herein has a shear rate of 10000s -1 and a viscosity of 0.3 Pa·s or less. This 10000s -1 The shear rate of is assumed to be the shear rate when the paste adhering to the outside of the cylinder cells is scraped off with a doctor blade. In other words, the conductive paste disclosed herein is characterized by exhibiting low-viscosity behavior when being scraped off by a doctor blade. As a result, when the paste adhering to the outside of the cells is scraped off by the doctor blade, it easily fills the inside of the cells, so that the occurrence of transfer defects can be suppressed. Note that at a shear rate of 10000s -1 the viscosity is preferably 0.27 Pa·s or less, more preferably 0.25 Pa·s or less, still more preferably 0.22 Pa·s or less, and particularly preferably 0.2 Pa·s or less. Thereby, transfer defects in gravure printing can be more suitably suppressed. On the other hand, at a shear rate of 10000s -1 the lower limit of the viscosity is not particularly limited, and may be 0.01 Pa·s or more, 0.02 Pa·s or more, 0.04 Pa·s or more, or 0.06 Pa·s or more.
[0011] Note that in this specification, the simple reference to "viscosity" refers to the viscosity at a shear rate of 10000s -1 The "viscosity at" refers to the viscosity at this "shear rate of 10000s -1 The "viscosity at" is measured according to the following procedure. First, the sample to be measured is held in a constant temperature bath at 25°C for 10 hours or more. Next, the paste taken out of the constant temperature bath is stirred about 10 times with a spatula. Then, using a rotational oscillation rheometer MARS iQ AIR manufactured by HAAKE, the shear rate is set to 0.01s -1 and increased to 10000s -1The viscosity is measured when this state is reached. The measurement conditions at this time are set as follows. Measurement mode: Shear rate dependency measurement Cone plate: 35 mm diameter, 0.5° angle Gap: 0.027 mm Measurement time: 2 minutes Measurement temperature: 25°C
[0012] Furthermore, the conductive paste disclosed herein has a phase angle δ (hereinafter also referred to as "viscoelasticity δ") of 45° or less when dynamic viscoelasticity measurement is performed at a frequency of 0.1 Hz. This frequency of 0.1 Hz assumes the vibration speed (angular frequency) when the conductive paste is transferred to a substrate. That is, in the technology disclosed herein, the viscoelasticity δ of the conductive paste at the time of transfer to the substrate is specified. A paste with a small viscoelasticity δ responds elastically to vibration during transfer, and thus can suppress the occurrence of saddle standing. Specifically, a paste that exhibits viscous behavior during transfer tends to remain in the cells (particularly in the central portion of the cells) when transferred to the substrate surface. As a result, the amount of paste in the central portion in the width direction after transfer decreases, leading to saddle standing in the printed paste. On the other hand, a paste that exhibits elastic behavior during transfer hardly remains in the cells (particularly in the central portion of the cells) when transferred to the substrate surface, so that saddle standing is less likely to occur. The viscoelasticity δ of the conductive paste is preferably 44° or less, more preferably 43° or less, still more preferably 42° or less, and particularly preferably 40° or less. Thereby, the occurrence of saddle standing can be more favorably suppressed. On the other hand, if the conductive paste becomes too elastic, there is a risk that the conductive paste cannot be removed from the cells during transfer. From this viewpoint, the lower limit of the viscoelasticity δ is preferably 1° or more, more preferably 3° or more, still more preferably 5° or more, and particularly preferably 8°Pa·s or more.
[0013] As described above, in the present specification, the phase angle δ when dynamic viscoelasticity measurement is performed at a frequency of 0.1 Hz is referred to as "viscoelastic δ". This "phase angle δ when dynamic viscoelasticity measurement is performed at a frequency of 0.1 Hz" is measured according to the following procedure. First, the sample to be measured is held in a constant temperature bath at 25°C for 10 hours or more. Next, the paste taken out from the constant temperature bath is stirred about 10 times with a spatula. Then, the viscoelastic δ is measured using a rotational vibration type rheometer MARS iQ AIR manufactured by HAAKE. In the measurement of viscoelastic δ, the measurement is performed at the time point when the frequency is 0.1 Hz while increasing the frequency from 0.01 Hz to 100 Hz. The measurement conditions at this time are set as follows. Measurement mode: Frequency dependency measurement Cone plate: Diameter 35 mm, angle 0.5° Gap: 0.027 mm Measurement time: 27 minutes Measurement temperature: 25°C
[0014] 2. Components of conductive paste As described above, the conductive paste disclosed herein includes conductive particles, dielectric particles, a binder resin, and a dispersion medium. In addition, the conductive paste disclosed herein may further contain an acid-based dispersant and an amine-based compound. Hereinafter, each component will be described.
[0015] (1) Conductive particles The conductive particles are particles constituting the main component of the electrode layer after firing. The type of the conductive particles is not particularly limited, and can be appropriately selected from conventionally known materials that can constitute the electrode layer of electronic components. Examples of the metal element contained in the conductive particles include nickel (Ni), aluminum (Al), copper (Cu), tungsten (W), gold (Au), silver (Ag), platinum (Pt), palladium (Pd), rhodium (Rh), iridium (Ir), ruthenium (Ru), osmium (Os) and the like. Further, the conductive particles may be a mixture or alloy of these metal elements. Among these, nickel is particularly suitable as a material for conductive particles because it has an excellent balance between material cost and conductive performance.
[0016] The average particle diameter of the conductive particles is preferably 1 μm or less, more preferably 0.8 μm or less, even more preferably 0.6 μm or less, and particularly preferably 0.4 μm or less, for example, 0.3 μm or less. This contributes to the thinning of the electrode layer after firing and improvement of surface smoothness. On the other hand, the lower limit of the average particle diameter of the conductive particles is preferably 0.01 μm or more, more preferably 0.05 μm or more, and particularly preferably 0.1 μm or more. This suppresses the aggregation of conductive particles, thus contributing to the improvement of the homogeneity of the electrode layer. In this specification, "average particle diameter" refers to the particle size corresponding to the cumulative 50% from the smallest particle size in the particle size distribution based on the number of particles observed using an electron microscope.
[0017] Furthermore, the content of conductive particles is preferably 30% by mass or more, more preferably 35% by mass or more, even more preferably 40% by mass or more, and particularly preferably 45% by mass or more. As the content of conductive particles in the conductive paste increases, the conductivity of the electrode layer after firing tends to improve. On the other hand, the upper limit of the content of conductive particles is preferably 65% by mass or less, more preferably 60% by mass or less, even more preferably 55% by mass or less, and particularly preferably 50% by mass or less. As the content of conductive particles decreases, the viscosity of the conductive paste decreases, which tends to make it easier to scrape with a doctor blade. In this specification, "content" refers to the mass ratio when the total amount of conductive paste is set to 100% by mass, unless otherwise specified.
[0018] (2) Dielectric particles Dielectric particles are inorganic particles with a lower thermal shrinkage rate than conductive particles. These dielectric particles are added to mitigate the thermal shrinkage of the conductive paste during firing. This suppresses the occurrence of cracks due to rapid thermal shrinkage. The material of the dielectric particles is not particularly limited and can be appropriately selected from conventionally known materials. Examples of dielectric particles include barium titanate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, zirconium titanate, zinc titanate, barium magnesium niobate, calcium zirconate, strontium zirconate, titanium dioxide, titanium pentoxide, hafnium oxide, zirconium oxide, aluminum oxide, forsterite, niobium oxide, and barium neodymate titanate. In some electronic components, such as MLCCs, a dielectric layer is formed adjacent to the conductive layer. In such cases, it is preferable to use the same material for the dielectric particles in the conductive paste as for the dielectric layer. This prevents cracks caused by differences in thermal shrinkage behavior between the conductive layer and the dielectric layer.
[0019] The average particle diameter of the dielectric particles is preferably 0.5 μm or less, more preferably 0.4 μm or less, even more preferably 0.3 μm or less, and particularly preferably 0.2 μm or less. This contributes to the thinning of the electrode layer after firing and improvement of surface smoothness. On the other hand, the lower limit of the average particle diameter of the dielectric particles is preferably 0.005 μm or more, more preferably 0.01 μm or more, even more preferably 0.02 μm or more, and particularly preferably 0.05 μm or more. This suppresses the aggregation of dielectric particles.
[0020] Furthermore, the content of dielectric particles is preferably 0.5% by mass or more, more preferably 1% by mass or more, even more preferably 1.5% by mass or more, and particularly preferably 2% by mass or more. As the content of dielectric particles increases, it becomes easier to suppress rapid thermal shrinkage during firing. On the other hand, the upper limit of the content of dielectric particles is preferably 15% by mass or less, more preferably 13% by mass or less, and particularly preferably 10% by mass or less. As the content of dielectric particles decreases, the conductivity of the conductive layer after firing tends to improve. Furthermore, when the content of conductive particles is 100 parts by mass, the content of dielectric particles is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and particularly preferably 3 parts by mass or more. On the other hand, when the content of conductive particles is 100 parts by mass, the upper limit of the content of dielectric particles is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, and particularly preferably 20 parts by mass or less.
[0021] (3) Binder resin Binder resins are added to impart tackiness to the substrate and to maintain the shape of the conductive paste (dried film) after drying. Binder resins also have the function of adjusting the viscosity of the conductive paste. Examples of binder resins include cellulose resin, polyvinyl acetal resin, polyvinyl alcohol resin, acrylic resin, urethane resin, epoxy resin, phenolic resin, rosin resin, polyester resin, and ethylene resin. The binder resin may also be a mixture of two or more of these resin materials. A preferred example of a binder resin is a mixture of cellulose resin and polyvinyl acetal resin. Cellulose resin exhibits rigid properties and therefore has the function of making the conductive paste elastic. On the other hand, polyvinyl acetal resin exhibits flexible properties and therefore has the function of making the conductive paste viscous. That is, a binder resin mixture of cellulose resin and polyvinyl acetal resin exhibits suitable viscoelasticity δ during transfer, thus contributing to the suppression of saddle formation.
[0022] In this specification, "cellulose resin" is a concept that includes not only linear polymers (cellulose) containing β-glucose as repeating units, but also derivatives of said cellulose. Examples of such cellulose resins include methylcellulose, ethylcellulose, hydroxymethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, hydroxypropylmethylcellulose, carboxymethylcellulose, carboxyethylcellulose, carboxyethylmethylcellulose, cellulose acetate phthalate, and nitrocellulose. Among these, methylcellulose and ethylcellulose are particularly preferred as cellulose resins from the viewpoint of more favorably improving the elasticity of the conductive paste.
[0023] On the other hand, the term "polyvinyl acetal resin" is a concept that encompasses not only compounds obtained by acetalizing polyvinyl alcohol resin (polyvinyl acetal), but also derivatives of said polyvinyl acetal. Preferred examples of this polyvinyl acetal resin include polyvinyl butyral (PVB), polyvinyl formal, polyvinyl benzal, polyvinyl isobutyral, polyvinyl acetoacetal, polyvinyl phenyl acetal, and polyvinyl acetobutyral. Among these, polyvinyl butyral resin is particularly preferred from the viewpoint of more favorably improving the viscosity of the conductive paste.
[0024] Furthermore, the binder resin of the conductive paste disclosed herein is more preferably a mixture of cellulose resin and polyvinyl acetal resin in a predetermined ratio. This makes it easier to realize a conductive paste in which the viscoelasticity δ is controlled to a desired range (e.g., 45° or less). Specifically, the ratio of the cellulose resin content C to the total amount of cellulose resin content C and polyvinyl acetal resin content D (C / C+D) is preferably 0.1 or more, more preferably 0.2 or more, and particularly preferably 0.3 or more. This allows for the imparting of suitable elasticity to the conductive paste. On the other hand, the above ratio (C / C+D) may be 1.0 or less, preferably 0.8 or less, more preferably 0.7 or less, even more preferably 0.6 or less, and particularly preferably 0.5 or less. This allows for the imparting of suitable viscosity to the conductive paste.
[0025] Furthermore, in the conductive paste disclosed herein, it is preferable to adjust the degree of polymerization of the binder resin to a predetermined range. This allows for a shear rate of 10,000 s. -1 Conductive pastes with viscosity controlled to a desired range (e.g., 0.3 Pa·s or less) can be more easily realized. For example, the weight-average molecular weight (Mw) of the cellulose resin may be 5,000 or more, 10,000 or more, or 15,000 or more. Also, the weight-average molecular weight (Mw) of the cellulose resin may be 250,000 or less, 240,000 or less, or 230,000 or less. On the other hand, the weight-average molecular weight (Mw) of the polyvinyl acetal resin may be 5,000 or more, 10,000 or more, or 15,000 or more. Also, the weight-average molecular weight (Mw) of the cellulose resin may be 300,000 or less, 200,000 or less, or 100,000 or less.
[0026] Also, shear rate 10000s -1The viscosity can also be affected by the binder resin content. Specifically, when the total amount of conductive particles is 100% by mass, the binder resin content is preferably less than 8% by mass, more preferably 7.5% by mass or less, and particularly preferably 7% by mass or less. As the binder resin content decreases, the viscosity of the conductive paste tends to decrease. On the other hand, from the viewpoint of maintaining the shape of the dried film, the binder resin content is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1.0% by mass or more, and particularly preferably 2% by mass or more.
[0027] (4) Dispersion medium The dispersion medium is a liquid that disperses conductive particles and dielectric particles (hereinafter collectively referred to as "inorganic particles"). The dispersion medium also functions as a solvent that dissolves organic components in the paste (binder resin, dispersant, amine compounds, etc.). The type of dispersion medium is not particularly limited and can be appropriately selected from conventionally known organic solvents. Examples of dispersion mediums include alcohol-based solvents, ether-based solvents, ester-based solvents, and hydrocarbon-based solvents. Specific examples of dispersion mediums include terpineol, texanol, dihydroterpineol, benzyl alcohol, 3-methoxy-3-methyl-1-butanol, phenoxyethanol, 1-phenoxy-2-propanol, isoborneol, diethylene glycol, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether (butyl carbitol), propylene glycol monobutyl ether, and dipropylene glycol methyl-n-propyl ether. Examples of ester-based dispersion media include 3-methoxy-3-methyl-1-butanol acetate, 3-methoxybutyl acetate, 3-methoxy-3-methylbutyl acetate, ethylene glycol monomethyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol diacetate, cyclohexanol acetate, isobornyl acetate, carbitol acetate, ethyl diglycol acetate, butyl glycol acetate, butyl diglycol acetate, butyl cellosolve acetate, diethylene glycol monobutyl ether acetate (butyl carbitol acetate), terpineol acetate, and dihydroterpineol acetate. Other specific examples of dispersion media include toluene, xylene, normal paraffin, isoparaffin, monocyclic naphthenes, bicyclic naphthenes, and mineral spirits.
[0028] The content of the dispersion medium is preferably 25% by mass or more, more preferably 30% by mass or more, even more preferably 35% by mass or more, and particularly preferably 40% by mass or more. As the content of the dispersion medium increases, the viscosity of the paste tends to decrease. On the other hand, from the viewpoint of fixation after printing and shape retention, the content of the dispersion medium is preferably 70% by mass or less, more preferably 65% by mass or less, and particularly preferably 60% by mass or less.
[0029] (5) Dispersant Dispersants are organic compounds that improve the dispersibility of conductive particles and dielectric particles. Specifically, dispersants adhere to the surface of inorganic particles, causing steric hindrance. This suppresses the precipitation and aggregation of inorganic particles. In the conductive paste disclosed herein, it is preferable to use an acidic dispersant. This acidic dispersant allows the acidic group portion of the organic component to act on the surface of the inorganic particle, suitably increasing the affinity between the inorganic and organic components. For this reason, acidic dispersants are suitably used in conductive pastes for gravure printing. On the other hand, adding an acidic dispersant increases the acid value of the conductive paste. This weakens the interaction between particles, improving the overall fluidity of the paste and making it more viscous. As a result, saddle formation is more likely to occur in the conductive paste after transfer. However, the conductive paste disclosed herein can suppress viscosity during transfer even when using an acidic dispersant, thus preventing saddle formation after transfer. Details of this point will be described later.
[0030] Examples of acidic dispersants include carboxylic acid-based dispersants, phosphoric acid-based dispersants, and sulfonic acid-based dispersants. These acidic dispersants tend to promote viscosity increase in conductive pastes, while also exhibiting the effect of improving the affinity between inorganic and organic components as described above, making them particularly suitable for use in the conductive pastes disclosed herein. Carboxylic acid-based dispersants contain a carboxyl group (COO) in their molecule. - It is an organic compound having a phosphonic acid group (PO3) in its molecule. Phosphate-based dispersants are organic compounds having a phosphonic acid group (PO3) in their molecule. - base, PO3 2-It is an organic compound having a sulfonic acid group (SO3) in its molecule. Sulfonic acid dispersants are organic compounds having a sulfonic acid group (SO3) in their molecule. - group, SO3 2- These are organic compounds having a group. Among these, carboxylic acid-based dispersants are particularly suitable for use in the conductive paste disclosed herein. Specific examples of these carboxylic acid-based dispersants include EfkaFA4673 (molecular weight 13,000).
[0031] When a carboxylic acid-based dispersant is used as the dispersant, the weight-average molecular weight is preferably 3000 or more, more preferably 5000 or more, even more preferably 8000 or more, and particularly preferably 10000 or more. The daily stability of the conductive paste tends to improve as the weight-average molecular weight of the carboxylic acid-based dispersant increases. On the other hand, the upper limit of the weight-average molecular weight of the carboxylic acid-based dispersant is preferably 50000 or less, more preferably 30000 or less, even more preferably 20000 or less, and particularly preferably 15000 or less. As the weight-average molecular weight of the carboxylic acid-based dispersant decreases, the viscosity of the conductive paste tends to decrease, which can contribute to improved printability.
[0032] In the technology disclosed herein, it is preferable to appropriately change the type and amount of acidic dispersant added so that the acid value of the conductive paste falls within a predetermined range. For example, the acid value of the conductive paste per 1 wt% of conductive particles is preferably 100 mg KOH / g or less, more preferably 75 mg KOH / g or less, even more preferably 55 mg KOH / g or less, and particularly preferably 30 mg KOH / g or less. This makes it easier to suppress the viscosity of the conductive paste. On the other hand, the lower limit of the acid value of the conductive paste is not particularly limited and may be 1 mg KOH / g or more, 5 mg KOH / g or more, 10 mg KOH / g or more, or 14 mg KOH / g or more.
[0033] Furthermore, the content of the acidic dispersant is preferably 5% by mass or less, more preferably 3% by mass or less, even more preferably 2% by mass or less, and particularly preferably 1.5% by mass or less, for example, 1% by mass or less. As the content of the acidic dispersant decreases, the viscosity of the conductive paste is more easily suppressed. On the other hand, from the viewpoint of more favorably exhibiting the effect of improving the affinity between inorganic and organic components by the acidic dispersant, the content of the acidic dispersant is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.1% by mass or more, and particularly preferably 0.15% by mass or more, for example, 0.2% by mass or more. According to the technology disclosed herein, even when such a large amount of acidic dispersant is added, saddle formation due to viscosity of the conductive paste can be suppressed.
[0034] Furthermore, the dispersant is not limited to the acidic dispersants described above. For example, the dispersant may include dispersants other than acidic dispersants, as long as they do not significantly impair the effects of the technology disclosed herein. Examples of dispersants other than acidic dispersants include cationic dispersants, nonionic dispersants, and inorganic dispersants.
[0035] (6) Amine compounds The conductive paste disclosed herein preferably further contains an amine compound. Herein, "amine compound" refers to an organic compound having an amine group (-NH2, -NH-). The amine group of this amine compound neutralizes the acidic group (carboxyl group, phosphonic acid group, sulfonic acid group, etc.) of the acidic dispersant. This suppresses the viscosity increase of the conductive paste during transfer and promotes elasticity. As a result, even though an acidic dispersant is used, the viscoelasticity δ at a frequency of 0.1 Hz can be easily controlled to a desired range (e.g., 45° or less). In other words, by using an acidic dispersant and an amine compound in combination, the advantages of an acidic dispersant, such as inhibiting contact between inorganic particles and preventing the generation of coarse particles due to aggregation, can be obtained, while also easily suppressing saddle formation after printing.
[0036] Any amines known conventionally can be used as amine compounds without particular limitations. For example, primary amines include methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, benzylamine, and cyclohexylamine. Secondary amines include dimethylamine, diethylamine, methylethylamine, dipropylamine, dibutylamine, methylbutylamine, di(2-ethylhexyl)amine, and dicyclohexylamine. Tertiary amines include trimethylamine, triethylamine, dimethylethylamine, dimethylbutylamine, diethylmethylamine, and tributylamine. Among these, primary and secondary amines can more effectively improve the viscoelasticity of the conductive paste.
[0037] In the technology disclosed herein, it is preferable to appropriately change the type and amount of amine compound added so that the amine value of the conductive paste falls within a predetermined range. For example, the amine value of the conductive paste per 1 wt% of conductive particles is preferably 50 mg KOH / g or more, more preferably 100 mg KOH / g or more, even more preferably 250 mg KOH / g or more, and particularly preferably 500 mg KOH / g or more. This can reduce the viscoelasticity δ of the conductive paste (promote elasticity). On the other hand, experiments by the inventors have confirmed that if the amine value of the conductive paste becomes too high, the viscoelasticity δ of the conductive paste actually increases (viscosity is promoted). From this viewpoint, the upper limit of the amine value of the conductive paste is preferably 4000 mg KOH / g or less, more preferably 3500 mg KOH / g or less, even more preferably 3000 mg KOH / g or less, and particularly preferably 2500 mg KOH / g or less.
[0038] Furthermore, it is preferable that the conductive paste disclosed herein has a ratio of amine value B to acid value A, B / A, adjusted to a predetermined range. This allows the amine group of the amine compound to appropriately neutralize the acidic group of the acidic dispersant, thereby promoting the elasticization of the conductive paste during transfer. The ratio of amine value B to acid value A, B / A, may be 4 or higher, 5 or higher, preferably 6 or higher, more preferably 10 or higher, even more preferably 12 or higher, and particularly preferably 15 or higher. This further promotes the elasticization of the conductive paste. On the other hand, from the viewpoint of suppressing viscosity due to an excessive increase in amine value, the upper limit of the above ratio B / A is preferably 250 or less, more preferably 220 or less, even more preferably 200 or less, and particularly preferably 190 or less.
[0039] (7) Other additives Furthermore, the conductive paste may use conventionally known additives as appropriate, provided that they do not significantly impair the effects of the technology disclosed herein. Examples of such additives include plasticizers, viscosity modifiers, thickeners, defoamers, leveling agents, pH adjusters, stabilizers, antioxidants, preservatives, and colorants (pigments, dyes, etc.).
[0040] [Applications of conductive paste] Next, gravure printing using the conductive paste disclosed herein will be described. Figure 1 is a schematic diagram showing an example of a gravure printing apparatus. In Figure 1, the symbol X indicates the width direction and the symbol Y indicates the height direction. As shown in Figure 1, the gravure printing apparatus 100 includes a tank 10, a cylinder 20, a doctor blade 30, and a guide roller 40.
[0041] Tank 10 is a container for storing conductive paste P. Specifically, Tank 10 is a box-shaped container with an opening 12 on its top surface.
[0042] The cylinder 20 is a cylindrical printing cylinder. The cylinder 20 is configured to rotate around its axis 20c. The outer circumferential surface 20a of the cylinder 20 is provided with cells 22 that are recessed from the outer circumferential surface 20a. These cells 22 are formed in a pattern corresponding to the shape of the printing purpose (conductive layer). The width w of the cells 22 is approximately 0.1 mm to 6.4 mm. The lower part of the cylinder 20 is placed inside the tank 10 through an opening 12. As a result, a portion of the outer circumferential surface 20a of the cylinder 20 is immersed in the conductive paste P inside the tank 10. When the cells 22 of the cylinder 20 are immersed in the conductive paste P, the conductive paste P fills the inside of the cells 22.
[0043] The doctor blade 30 is a thin plate extending in the direction of extension of the axis 20c of the cylinder 20 (perpendicular to the plane of the paper in Figure 1). The tip 32 of this doctor blade 30 is in contact with the outer surface 20a of the cylinder 20. When the cylinder 20 is rotated in this state, the conductive paste P that has spilled out of the cell 22 is scraped off by the doctor blade 30. Here, in a typical gravure printing apparatus 100, the shear rate when the doctor blade 30 scrapes off the conductive paste P is 1000s. -1 ~100,000s -1 To that extent. In contrast, the conductive paste P disclosed herein has a shear rate of 10,000 s. -1 The viscosity is controlled to be 0.3 Pa·s or less. In other words, the conductive paste P disclosed herein is prepared to exhibit low viscosity behavior when scraped by the doctor blade 30. This makes it easier for the scraped conductive paste P to fill the cell 22 when the conductive paste P outside the cell 22 is scraped by the doctor blade 30. Therefore, the conductive paste P disclosed herein can suppress defects (transfer defects) in which a sufficient amount of paste is not transferred to the substrate.
[0044] The guide roller 40 is a roller that guides the strip-shaped substrate S to a desired transport position. The guide roller 40 is positioned so that the transported substrate S is in contact with the outer circumferential surface 20a of the cylinder 20. Specifically, the guide roller 40 shown in Figure 1 is facing the top of the cylinder 20. The substrate S is transported between the cylinder 20 and the guide roller 40. The guide roller 40 transports the strip-shaped substrate S while pressing it against the outer circumferential surface 20a of the cylinder 20. At this time, when the substrate S comes into contact with the conductive paste P in the cell 22, the conductive paste P is transferred to the surface of the substrate S.
[0045] In a typical gravure printing apparatus, the vibration speed (angular frequency) when transferring the conductive paste P is approximately 0.01 Hz to 1 Hz. Conductive paste P with high viscoelasticity δ at a frequency of 0.1 Hz (exhibiting viscous behavior during transfer) tends to adhere to the inner wall 22a of the cell 22. Furthermore, conductive paste P with high viscoelasticity δ tends to remain inside the cell 22 (especially in the central part of the cell 22) when transferred to the surface of the substrate S. In other words, when conductive paste P with high viscoelasticity δ is transferred to the substrate S, saddle formation is likely to occur after transfer. On the other hand, the conductive paste P disclosed herein has a viscoelasticity of 45° or less at a frequency of 0.1 Hz. That is, the conductive paste P disclosed herein exhibits elastic behavior when transferred to the substrate S. Such conductive paste P with low viscoelasticity δ is less likely to remain inside the cell during transfer, thus suppressing saddle formation after transfer.
[0046] As described above, the conductive paste P disclosed herein can withstand a shear rate of 10,000 s in an environment of 25°C. -1 The viscosity measured is 0.3 Pa·s or less, and the phase angle δ when dynamic viscoelasticity measurement is performed at a frequency of 0.1 Hz is 45° or less. This suppresses both transfer defects and saddle formation in gravure printing.
[0047] The conductive paste disclosed herein can be used in the manufacture of various ceramic electronic components. In this specification, "ceramic electronic component" encompasses electronic components in general that have a crystalline ceramic substrate and / or an amorphous ceramic substrate. For example, ceramic capacitors, chip inductors, high-frequency filters, high-temperature co-fired ceramic (HTCC) substrates, low-temperature co-fired ceramic (LTCC) substrates, etc., which include ceramic substrates, are typical examples of "ceramic electronic components" as defined herein. Among these, the manufacture of MLCCs requires the formation of very small electrode layers (width: 0.1 mm to 6.4 mm, thickness: 0.2 μm to 3.0 μm). As a result, the cells 22 of the cylinder 20 become small and complex, making them prone to transfer defects and saddle formation. In contrast, the conductive paste disclosed herein can suitably suppress transfer defects and saddle formation in gravure printing, as described above. That is, the conductive paste disclosed herein can be particularly suitably used in the manufacture of MLCCs using gravure printing.
[0048] [Example Test] Next, we will describe some test examples relating to the technology disclosed herein. However, the following description is not intended to limit the technology disclosed herein to the content of these test examples.
[0049] 1. Sample preparation In this study, 31 different conductive pastes (Samples 1-31) with varying compositions were prepared. The compositions of the conductive pastes are shown in Table 1. As shown in Table 1, nickel particles with an average particle size of 0.2 μm were used as conductive particles in this study. Barium titanate powder with an average particle size of 0.1 μm was used as dielectric particles. A carboxylic acid-based dispersant (EfkaFA4673 (molecular weight 13,000)) was used as the dispersant. A mixture of ethyl cellulose and polyvinyl butyral was used as the binder resin. A mixture of dihydroterpineol, 3-methoxy-3-methylbutyl acetate, and a naphthenic solvent in a ratio of 60:20:20 was used as the dispersion medium. Furthermore, in this study, one amine compound was selected from di(2-ethylhexyl)amine, dicyclohexylamine, and propylamine.
[0050] In this test, the conductive particle content was set to 48 wt% and the dielectric particle content to 2 wt% relative to the total amount (100 wt%) of the conductive paste. On the other hand, the content and mixing ratio of the dispersant, binder resin, and amine compound were varied for each sample. After changing the content of these materials, the remainder was used as the content of the dispersion medium. As a result, 31 types of conductive pastes (Samples 1-31) were obtained with different parameters: "binder resin content relative to nickel particle content (Ni wt%)", "degree of polymerization of binder resin", "amine value B (Ni wt%)", "acid value A (Ni wt%)", and "cellulose resin content ratio in binder resin (C / (C+D))". These parameters are shown in Table 1.
[0051] 2. Analysis of the paste (1) Measurement of paste viscosity Using a HAAKE MARS iQ AIR rotary vibratory rheometer, the shear rate was 10,000 s. -1 The viscosity was measured. The measurement results are shown in Table 1. Note that the shear rate was 10000 s. -1 The viscosity was measured according to the measurement procedure described above.
[0052] (2) Dynamic viscoelasticity measurement Similar to the paste viscosity described above, the phase angle δ (viscoelasticity δ) at a frequency of 0.1 Hz was measured using a MARS iQ AIR from HAAKE. The measurement results are shown in Table 1. The viscoelasticity δ was measured according to the measurement procedure described above.
[0053] 3. Evaluation Test In this evaluation, coating films were formed using the following procedure, and the surface roughness of the coating films was measured. Specifically, first, a dielectric green sheet containing barium titanate was prepared. Next, the conductive paste of each sample was applied to the dielectric green sheet using gravure printing, and a coating film of approximately 1 μm was formed by drying at 80°C for approximately 5 minutes. The gravure printing conditions were as follows. Printing pattern: 1005 type (2000 μm x 500 μm) Printing speed: 30m / min Printing pressure: 0.2 MPa
[0054] Next, in this test, the state of the dried film in each sample was evaluated. Here, if a dried film corresponding to the pattern in cell 22 was formed, it was evaluated as "Transfer: ○". On the other hand, if there were areas with insufficient transfer within the pattern corresponding to cell 22, it was evaluated as "Transfer: ×". Furthermore, in this test, the cross-section of the dried film was observed with an optical microscope. If saddles of 0.1 μm or more were formed at both ends of the dried film, it was evaluated as "Saddle formation: ×". On the other hand, if the height of the saddle was less than 0.1 μm, it was evaluated as "Saddle formation: ○". The evaluation results are shown in Table 1.
[0055] [Table 1]
[0056] As shown in Table 1, both transfer failure and saddle upright were well suppressed in samples 5-9, 12-18, 20, 22, 24-27, and 29-31. Furthermore, a comparison of sample 21 with the other samples showed that at a shear rate of 10,000 s, -1It was found that transfer failures could be suppressed when the viscosity was 0.3 Pa·s or less. However, in sample 21, where the viscosity was greater than 0.3 Pa·s, transfer failures occurred because a sufficient amount of paste was not transferred to the substrate, making it impossible to investigate saddle formation. Furthermore, at a shear rate of 10000 s², -1 It was found that the viscosity could be controlled by adjusting the binder resin content. On the other hand, by comparing samples 1-4, 10-11, 19, 23, and 28 with other samples, it was found that saddle formation could be suppressed when the viscoelasticity δ at a frequency of 0.1 Hz was 45° or less. Furthermore, it was found that this viscoelasticity δ could be controlled by adjusting the ratio of acid value A to amine value B (B / A) and the cellulose resin content ratio (C / (C+D)).
[0057] The specific examples of the technology disclosed herein have been described in detail above, but these are merely illustrative and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes to the specific examples illustrated above. For example, the technology disclosed herein encompasses the embodiments described in items 1 to 10 below.
[0058] [Item 1] A conductive paste for gravure printing comprising at least conductive particles, dielectric particles, a binder resin, and a dispersion medium, Shear rate 10000s -1 The viscosity in is 0.3 Pa·s or less, and A conductive paste in which the phase angle δ is 45° or less when dynamic viscoelasticity measurement is performed at a frequency of 0.1 Hz.
[0059] [Item 2] The conductive paste described in item 1, wherein the phase angle δ when dynamic viscoelasticity measurement is performed at the aforementioned frequency of 0.1 Hz is 5° or more.
[0060] [Item 3] A conductive paste according to item 1 or 2, further comprising an acidic dispersant and an amine compound.
[0061] [Item 4] A conductive paste as described in item 3, wherein the ratio of amine value B to acid value A, B / A, is between 4 and 250.
[0062] [Item 5] The conductive paste according to item 3 or 4, wherein the acidic dispersant is at least one selected from the group consisting of carboxylic acid-based dispersants, phosphoric acid-based dispersants, and sulfonic acid-based dispersants.
[0063] [Item 6] The conductive paste according to item 5, wherein the weight-average molecular weight of the carboxylic acid-based dispersant is 10,000 to 20,000.
[0064] [Item 7] The conductive paste according to any one of items 3 to 6, wherein the amine compound is at least one selected from the group consisting of primary amines and secondary amines.
[0065] [Item 8] The conductive paste according to any one of items 1 to 7, wherein the binder resin comprises at least a cellulose resin and a polyvinyl acetal resin.
[0066] [Item 9] The conductive paste according to item 8, wherein the ratio of the cellulose resin content C to the total amount of the cellulose resin content C and the polyvinyl acetal resin content D (C / C+D) is 0.1 or more and 1.0 or less.
[0067] [Item 10] A conductive paste according to any one of items 1 to 9, wherein the content of the binder resin is 0.1% by mass or more and less than 8% by mass when the total amount of the conductive particles is 100% by mass. [Explanation of Symbols]
[0068] 10 tanks 12 Openings 20 cylinders 22 cells 22a Inner wall 30 Doctor Blade 40 Guide Rollers 100 Gravure printing machines P Conductive Paste S base material
Claims
1. A conductive paste for gravure printing comprising at least conductive particles, dielectric particles, a binder resin, and a dispersion medium, Shear rate 10000 s -1 The viscosity in is 0.3 Pa·s or less, and A conductive paste in which the phase angle δ is 45° or less when dynamic viscoelasticity measurement is performed at a frequency of 0.1 Hz.
2. The conductive paste according to claim 1, wherein the phase angle δ when dynamic viscoelasticity measurement is performed at the frequency of 0.1 Hz is 5° or more.
3. The conductive paste according to claim 1, further comprising an acidic dispersant and an amine compound.
4. The conductive paste according to claim 3, wherein the ratio of amine value B to acid value A, B / A, is 4 or more and 250 or less.
5. The conductive paste according to claim 3 or 4, wherein the acidic dispersant is at least one selected from the group consisting of carboxylic acid-based dispersants, phosphoric acid-based dispersants, and sulfonic acid-based dispersants.
6. The conductive paste according to claim 5, wherein the weight-average molecular weight of the carboxylic acid-based dispersant is 10,000 to 20,000.
7. The conductive paste according to claim 3 or 4, wherein the amine compound is at least one selected from the group consisting of primary amines and secondary amines.
8. The conductive paste according to claim 1, wherein the binder resin comprises at least one of a cellulose resin and a polyvinyl acetal resin.
9. The conductive paste according to claim 8, wherein the ratio of the cellulose resin content C to the total amount of the cellulose resin content C and the polyvinyl acetal resin content D (C / C+D) is 0.1 or more and 1.0 or less.
10. The conductive paste according to claim 1 or 9, wherein the content of the binder resin is 0.1% by mass or more and less than 8% by mass when the total amount of the conductive particles is 100% by mass.
Citation Information
Patent Citations
Conductive paste and method for producing electronic component using the same
JP2021051916A